Study on desulfurization mechanism of adsorbents prepared by high ratio circulating fly ash and lime. (1st October 2020) - Cui, S.; Niu, F.; Wang, N.J.; Zhou, J.M.; Wang, J.P.; Li, J.S.
Abstract: Under the conditions of low temperature, low humidity and different mixture ratios, a variety of adsorbents were prepared by using a new preparation method and the Shendong high ratio circulating fly ash of the No Gap Desulfurization process was chosen as raw material. The desulfurization performance of adsorbents were characterized by the fixed-bed desulfurization reactor, and the effects of desulfurization process conditions (moisture content, mixing ratio, desulfurization temperature and initial concentration of SO2 ) on desulfurization removal efficiency have been experimentally investigated. The optimum desulfurization process conditions were found under the conditions of the hydration time was 3 h, moisture content was 15%, desulfurization temperature was 70 °C and initial concentration was 200 μL/L, and at this time the effective desulfurization time was 93.95 min, the maximum desulfurization efficiency was 99.12%. Through systematic analysis of the whole process of desulfurization reaction, it was concluded that the desulfurization efficiency was controlled by the desulfurization reaction rate and gas diffusion rate at the initial and later stages of the reaction respectively. Reducing the difference between the desulfurization reaction rate and gas diffusion rate can improve the desulfurization efficiency, which laying a theoretical foundation to improve the desulfurization efficiency of No Gap Desulfurization process.